2008
DOI: 10.1097/prs.0b013e318180ed8b
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Denervation of Rectus Abdominis in DIEP Flap Harvest: The Importance of Medial Row Perforators

Abstract: The nerves innervating rectus abdominis are at risk during the raising of a DIEA perforator flap. These nerves enter the posterior surface of rectus abdominis and run with the most lateral branch of the DIEA and its perforators. Damage to these nerves may denervate rectus abdominis muscle and contribute to donor-site morbidity. As medial row perforators were not related to these motor nerves, these perforators are ideal for inclusion in DIEA perforator and transverse rectus abdominis myocutaneous flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 39 publications
1
51
1
3
Order By: Relevance
“…19,20 We used medial perforators for all our patients because studies have indicated that medial row perforators provide a wider area of perfusion than do lateral row perforators 21 and that their use helps avoid denervation of the rectus abdominus muscle. 22 As expected, marked contralateral venous congestion was the most common intraoperative finding with the clamp test. Attention was given to prevent flap hypothermia or physical stress to the perforator, and time was allowed for vascular equilibration.…”
Section: Discussionmentioning
confidence: 72%
“…19,20 We used medial perforators for all our patients because studies have indicated that medial row perforators provide a wider area of perfusion than do lateral row perforators 21 and that their use helps avoid denervation of the rectus abdominus muscle. 22 As expected, marked contralateral venous congestion was the most common intraoperative finding with the clamp test. Attention was given to prevent flap hypothermia or physical stress to the perforator, and time was allowed for vascular equilibration.…”
Section: Discussionmentioning
confidence: 72%
“…In fact, elevation of perforator flaps always requires meticulous dissection of the myocutaneous perforator(s) through the underlying muscle. Recent anatomical studies on cadavers indicate that use of the medial row of perforators reduce the potential risks of muscle denervation [22]. Motor nerve fibers run from lateral to medial beneath the muscle belly, so that harvesting DIEAP-ra based on lateral row perforators can expose the patient to muscle denervation and abdominal wall weakness.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic basis of using medial perforators for this reason has already been established in the literature. 9 Thus within the spectrum of DIEP harvest, donor site dissection has been minimized (only to be surpassed by SIEA flap harvest). This has resulted in improved confidence in bilateral cases, and reduction in fatigue, which better allows the surgeon to be creative during fabrication of the breast mound(s).…”
Section: Discussionmentioning
confidence: 99%
“…Similar dissections were then performed on the left side (Figs. 8,9). Figure 10 shows the vector of the right pedicle extraction, with the left side discontinuous incisions already repaired, and Figure 11 with both sides repaired.…”
Section: Example 2: Bilateral Diepmentioning
confidence: 98%